Dibenzothiophenes and benzo[b]naphthothiophenes: Molecular markers for tracing oil filling pathways in the carbonate reservoir of the Tarim Basin, NW China. (January 2016) - Fang, Ronghui; Wang, T.-G.; Li, Meijun; Xiao, Zhongyao; Zhang, Baoshou; Huang, Shaoying; Shi, Shengbao; Wang, Daowei; Deng, Weilong
Highlights: The Ordovician oils in the Halahatang Oilfield belong to the same oil family. Four indicators relative to DBTs and BNTs were used in tracing oil filling pathways. The overall oil migration orientation from south to north was confirmed. Preferred filling points were determined. The potential source kitchen is in the southern part of the Halahatang Oilfield. Abstract: Dibenzothiophenes (DBTs) and benzo[ b ]naphthothiophenes (BNTs) are the main sulfur-containing heterocyclic aromatic compounds in crude oils and sedimentary rock extracts. Because of the relatively higher electronegativity and an unshared pair of electrons in the outer shell orbital of the sulfur atom, hydrogen bonds can be formed between the sulfur and hydrogen atoms of the surrounding medium in carrier beds. Therefore, DBTs and BNTs are potential geochemical markers for tracing oil filling pathways. A correlation of oils in the Halahatang Oilfield of the Tabei Uplift in the Tarim Basin (NW China) shows that the molecular marker compositions of all oils are quite similar, implying that these oils have been sourced from the same source kitchen and belong to a same oil family. Using molecular indicators relative to DBTs and BNTs, namely, 4-/1-MDBT (4-/1-methyldibenzothiophene), 4, 6-/(1, 4 + 1, 6)-DMDBT (4, 6-/(1, 4 + 1, 6)-dimethyldibenzothiophene), (2, 6 + 3, 6)-/(1, 4 + 1, 6)-DMDBT ((2, 6 + 3, 6)-/(1, 4 + 1, 6)-dimethyldibenzothiophene), and [2, 1]BNT/([2, 1]BNT + [1, 2]BNT) (benzo[ b ]naphtho[2, 1- d ]thiophene/(benzo[ b ]naphtho[2, 1- d ]thiophene + benzo[ b ]naphtho[1, 2- d ]thiophene)), this paper traces the oil migration orientation and filling pathways in this oilfield. The isopleth maps of these molecular indicators unequivocally reveal an overall oil migration, filling points, and preferred filling pathways orientation from south to north. Based on this, a potential source kitchen is predicted in the southern part of the Halahatang Depression, most probably at the Manxi (Shuntuoguole) Low Uplift, just between the Awati and Manjiaer depressions. The southern part of the Halahatang Depression, along the oil charging pathways, is predicted to be the most promising region for oil exploration.